2009
DOI: 10.1007/s12011-009-8579-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Improves Protein Deposition Through Regulating the mRNA Levels of IGF-1, IGF-1R, and Ub in Rat Skeletal Muscle Cells

Abstract: The aim of this study was to evaluate the impact of three different chromium forms--chromic chloride (CrCl3), chromium picolinate (CrPic), and a newly synthesized complex of chromium chelated with small peptides (CrSP)--on protein metabolism in vitro. In cultured skeletal muscle cells, CrSP was able to increase the basal and insulin-stimulated levels of protein deposition in skeletal muscles cells. CrCl3 and CrPic augmented insulin-stimulated protein synthesis. At the molecular level, insulin significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…While the present results showed that graded levels of dietary chromium as CrMet have no significant effect on growth performance in either the individual period or total experimental period in pigs as body weights grow from 30 to 100 kg, as well as carcass traits, nevertheless, pigs fed 200 μg/kg chromium as CrMet had a numerically greater value in LMA than the control (P<0.10). A tendency to increase in LMA may be due to increased insulin activity by chromium which stimulates amino acid transport and protein synthesis in muscle cells [31], or increased secretions or mRNA levels of growth hormone and insulin like growth factor-I which accelerate protein anabolism [20,32,33]. Moreover, the present result of a numerical increase in the 10th rib fat in 200 μg/kg chromium groups (P<0.10) indicated that chromium addition may promote adipose lipogenesis, which was demonstrated by Lien et al [34] who found that long-term exposure to chromium picolinate (CrPic) in growing-finishing pigs increased the activities of adipose tissue lipogenesis related enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the present results showed that graded levels of dietary chromium as CrMet have no significant effect on growth performance in either the individual period or total experimental period in pigs as body weights grow from 30 to 100 kg, as well as carcass traits, nevertheless, pigs fed 200 μg/kg chromium as CrMet had a numerically greater value in LMA than the control (P<0.10). A tendency to increase in LMA may be due to increased insulin activity by chromium which stimulates amino acid transport and protein synthesis in muscle cells [31], or increased secretions or mRNA levels of growth hormone and insulin like growth factor-I which accelerate protein anabolism [20,32,33]. Moreover, the present result of a numerical increase in the 10th rib fat in 200 μg/kg chromium groups (P<0.10) indicated that chromium addition may promote adipose lipogenesis, which was demonstrated by Lien et al [34] who found that long-term exposure to chromium picolinate (CrPic) in growing-finishing pigs increased the activities of adipose tissue lipogenesis related enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors hypothesized that CrMet supplementation may influence the fatty acid compositions of fat in pigs. It has been also reported that Cr is able to increase the uptake of amino acid and protein deposition in rat skeletal muscle cells [19,20], which may stimulate protein anabolism to alter the body composition. CrMet addition may affect the amino acid profiles of skeletal muscle in pigs, which is rarely investigated.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the total Mb concentration in the longissimus muscle of the pig is a very important contributor to pork colour. Cr is essential for normal glucose metabolism, functioning as a part of the insulin signaling auto-amplification mechanism and improves insulin-stimulated amino acid uptake and protein synthesis and gene expression (Vincent et al, 2000; Peng et al, 2010). The present results showed the CIE a* increased linearly with increasing total Mb content.…”
Section: Discussionmentioning
confidence: 99%
“…Cr-picolinate was shown to induce various effects: increase in AMPKinase and p38 MAPkinase activities [20], increase in receptor phosphorylation [21] and increase in insulin receptor mRNA (in addition to mRNA for GLUT-4, glycogen synthase and UCP3)[22]. Increased synthesis of IGF receptors, able to functionally replace failing insulin receptors, was also described [23]. Changes in the environment of insulin receptors were shown as reductions in plasma membrane cholesterol [24,25], leading to improved cytoskeletal functioning and enhanced insulin sensitivity.…”
Section: Chromiummentioning
confidence: 99%